الدور الثقافي والسياسي للنخبة الجزائرية في تونس أحمد توفيق المدني أنموذجا 1900-1925م - هادية سمان; أمال بوطيب (جامعة الوادي - University of Eloued, 2025)
تهدف هذه الدراسة إلى تسليط الضوء على الدور المحوري الّذي لعبته النّخبة الجزائرية في تونس من خلال مقاومة الاستعمار الفرنسي ثقافيا وسياسيا، ومن أجل ترسيخ الهوية العربية الإسلامية، ومن أبرز المفكرين والمصلحين والذي لم يأخذ حقه في دراسات سابقة كثيرة وهو المؤرخ والصحفي"أحمد توفيق المدني " الذي كان نموذجا بارزا لهذه النخبة خلال الفترة 1900 إلى 1925، وهو ابن عائلة جزائرية هاجرت إلى تونس، من مواليد 1899 م بتونس، جمع بين الكتابة التاريخية والصحفية، اذ لعب دورا بارزا في اثراء الحياة الفكرية عبر مساهمته الفكرية ومشاركته في تأسيس الجمعيات والصحف التي كانت منابر للدعوة إلى الإصلاح والتغيير وتحرير المجتمع التونسي من قيود الاحتلال، ومن الناحية السياسية انخراطه في صفوف الحركات المناهضة للاحتلال خاصة من خلال نشاطه في الحزب الحر الدستوري، حيث سعى الى توعية الجماهير والدفاع عن قضايا الحرية، إلى أن نفي إلى الجزائر عام 1925م فكان المنفى منبرا للنضال والجهاد ليس في الجزائر وتونس فحسب بل على المستوى العربي. This study aims to shed light on the pivotal role played by the Algerian elite in Tunisia through their cultural and political resistance to French colonialism and their efforts to uphold the Arab-Islamic identity. Among the most prominent intellectuals and reformers—who has not received sufficient attention in many previous studies—is the historian and journalist Ahmed Toufik El Madani. El Madani was a prominent example of this elite during the period from 1900 to 1925. He was born in Tunis in 1899 to an Algerian family that had emigrated to Tunisia. He combined historical writing with journalism and played a significant role in enriching intellectual life through his contributions and his participation in the founding of associations and newspapers that served as platforms for calls for reform، change، and the liberation of Tunisian society from the constraints of colonialism.Politically، he was actively involved in anti-colonial movements، particularly through his activities within the Destour Party (Constitutional Liberal Party)، where he sought to raise public awareness and defend the causes of freedom. In 1925، he was exiled to Algeria، and exile became a new platform for struggle and resistance—not only in Algeria and Tunisia but also across the Arab world.
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: النخبة في تونس; الدور الثقافي; الدور السياسي; أحمد توفيق المدني; Ahmed Toufik El Madani: The Political Role; The Cultural Role; The Elite in Tunisia.